Vocational Outcomes After Traumatic Brain Injury; Prevalence and Risk Factors After 1 Year in a Multivariable Model. Issue 2 (28th March 2022) - Singh, Rajiv; Dawson, Jeremy; Basu, Subhashis; Humphries, Thomas J.; Mason, Suzanne; Lecky, Fiona
Abstract : Objective: To determine the prevalence of employment status (ES) or full-time study after traumatic brain injury (TBI) in a representative population and its predictive factors. Design: Prospective cohort study. Setting: Regional Major Trauma Centre. Participants : In total, 1734 consecutive individuals of working age, admitted with TBI to a Regional Trauma Centre, were recruited and followed up at 8 weeks and 1 year with face-to-face interview. Median age was 37.2 years (17.5-58.2); 51% had mild TBI, and 36.8% had a normal computed tomographic (CT) scan. Main Outcome Measure: Complete or partial/modified return to employment or study as an ordinal variable. Results: At 1 year, only 44.9% returned to full-time work/study status, 28.7% had a partial or modified return, and 26.4% had no return at all. In comparison with status at 6 weeks, 9.9% had lower or reduced work status. Lower ES was associated with greater injury severity, more CT scan abnormality, older age, mechanism of assault, and presence of depression, alcohol intoxication, or a psychiatric history. The multivariable model was highly significant ( P < .001) and had a Nagelkerke R 2 of 0.353 (35.3%). Conclusions: Employment at 1 year is poor and changes in work status are frequent, occurring in both directions. While associations with certain features may allow targeting of vulnerable individuals in future, the majority of model variance remains unexplained and requires further investigation.